The Impact of COVID-19 Social Isolation on Physical Activity and Sedentary Behavior in Brazilian Children and Adolescents - Miranda, Fernando Leite; Fernandes, Carlos Henrique; Meirelles, Lia Myiamoto; Faloppa, Flavio; Ejnisman, Benno; Cohen, Moises (Revista Brasileira de Ortopedia, 2025)
Objective To measure the impact of social isolation on physical activities and sedentary behavior in Brazilian children and adolescents. To assess whether factors such as age, gender, days of week, type of housing, and the population of the city also had an impact.Methods The study was approved by the Medical Ethics Committee, and consent from parents was obtained. A Google Form (Google LLC, Mountain View, CA, USA) was sent to parents by email and WhatsApp (Meta Platforms Inc., Menlo Park, CA, USA). Parents answered the C-PAQ.PT questions for two different periods of time, one month before and during social isolation.Results There was a statistically significant reduction in the mean physical activity (p < 0.001) and an increase in the mean sedentary activities (p < 0.001) on weekdays and weekends during social isolation. There was a greater reduction in basketball, handball, and running in the 10 to 14-year-old group, as well as playing in the playground in the 5-to-9-year-old group. There was a statistically significant decrease in the practice of tag and cycling, respectively, among females and males. We did not observe statistically significant differences between types of housing and the number of inhabitants in the city.Conclusion The C-PAQ.PT allowed a quantitative assessment to identify the variations in physical activities and sedentary behaviors during social isolation. We have observed that only two physical activities were impacted by gender. The changes were not influenced by the number of inhabitants in the city or the type of housing.
Keywords: adolescent; children; COVID-19; exercise; surveys and questionnaires